The Paradox of Masculinity: The Narrative Identities among the Elderly in Yogyakarta - Oktarizal Drianus; Elli Nur Hayati (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2021)
The hegemony of masculinity tends to benefit more on one side, man. It is interesting to observe the change of masculinity in men with time. The dynamics proceeded to pertain to the psychological, economic, social, and symbolic representation. This study aimed to reveal both the narrative identities of elderly masculinity and the psychological dynamics that accompanied the lifespan of an older man. This study used hermeneutic-phenomenological approaches, with critical narrative analysis developed from Paul Ricoeur’s hermeneutics. Five older men, who live in a geriatric house in Yogyakarta, participated in this study. The results showed that the face of elderly masculinity was paradoxical masculinity. At the ideal level, the older men appropriated hegemonic masculinity but at the level of reality, they were in the marginalized masculinity position. Masculine subjects had experienced the maturation effect of togetherness with their wife. Wife has been an important subject and medium for growing the elderly masculinity and maintaining traditional manhood. The Paradox and their intersection with the complexity of the psychological dynamics made older men offer wiser masculinity and transform into positive masculinity such as gratitude, acceptance of life, sincerity, and caring.